2019
DOI: 10.1029/2018jc014634
|View full text |Cite
|
Sign up to set email alerts
|

Seasonality of Warm Water Intrusions Onto the Continental Shelf Near the Totten Glacier

Abstract: Warm Modified Circumpolar Deep Water (MCDW) from the Southern Ocean drives rapid basal melt of the Totten Ice Shelf on the Sabrina Coast (East Antarctica), affecting the mass balance of the grounded Totten Glacier. Recent observations show that MCDW intrudes onto the continental shelf through a depression at the shelf break. Here we investigate such intrusions by combining (1) new oceanographic and bathymetric observations collected for two consecutive years by profiling floats in the depression south of the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
43
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(49 citation statements)
references
References 87 publications
(151 reference statements)
6
43
0
Order By: Relevance
“…A narrow eastward undercurrent has been documented in several areas around Antarctica, at the shelf break and continental slope, by closely spaced hydrographic measurements and high-resolution models (Heywood et al 1998;Smedsrud et al 2006;Nuñez-Riboni and Fahrbach 2009;Chavanne et al 2010;Silvano et al 2019). Based on our results and previous works (e.g., Walker et al 2013;Kimura et al 2017;Webber et al 2019), it may be concluded that this undercurrent feature is an important element of the oceanic heat delivery toward the ice shelves.…”
Section: Discussionsupporting
confidence: 84%
“…A narrow eastward undercurrent has been documented in several areas around Antarctica, at the shelf break and continental slope, by closely spaced hydrographic measurements and high-resolution models (Heywood et al 1998;Smedsrud et al 2006;Nuñez-Riboni and Fahrbach 2009;Chavanne et al 2010;Silvano et al 2019). Based on our results and previous works (e.g., Walker et al 2013;Kimura et al 2017;Webber et al 2019), it may be concluded that this undercurrent feature is an important element of the oceanic heat delivery toward the ice shelves.…”
Section: Discussionsupporting
confidence: 84%
“…Li et al () reported a mass loss from Totten of 6.8±2.2 Gt/year with an acceleration of 0.55±0.27 Gt/year 2 between 1989 and 2015. This acceleration in grounded ice flux has been linked to intrusions of warm Modified Circumpolar Deep Water (0–1 °C) into Totten's subice shelf cavity (Greenbaum et al, ; Li et al, ; Mohajerani et al, ; Rintoul et al, ; Silvano et al, , ). Additionally, a 1‐ to 3‐km retreat of the southernmost portion of Totten's grounding line was observed between 1996 and 2013, concurrent with changes in subshelf ocean temperature (Li et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Li et al (2016) reported a mass loss from Totten of 6.8 ± 2.2 Gt/year with an acceleration of 0.55 ± 0.27 Gt/year 2 between 1989 and 2015. This acceleration in grounded ice flux has been linked to intrusions of warm Modified Circumpolar Deep Water (0-1 • C) into Totten's subice shelf cavity (Greenbaum et al, 2015;Li et al, 2016;Mohajerani et al, 2018;Rintoul et al, 2016;Silvano et al, 2017Silvano et al, , 2019. Additionally, a 1-to 3-km retreat of the southernmost portion of (total 36) that predict at least 1-m grounded ice thinning by 2100.…”
Section: Introductionmentioning
confidence: 99%